Effects of Mandelic and Propane-1,2,3-Tricarboxylic Acids on Calcium Oxalate Monohydrate Crystallization - SAYAN, PERVİZ; POLAT, SEVGİ (My University, 2020)
The effects of mandelic and propane-1,2,3-tricarboxylic acids as additives on calcium oxalate monohydrate (COM) crystals were investi-gated in this study. The physicochemical properties of the COM crystals prepared with and without these additives were characterized us-ing X-ray powder diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and zeta po-tential analysis. The XRD and SEM results showed that the crystals prepared in pure medium were monohydrates and consisted primarily of hexagonal crystals, respectively. The additives mandelic acid and propane-1,2,3-tricarboxylic acid in the crystallization media signifi-cantly changed the size and morphology of the COM crystals, the effects of which were more pronounced with higher concentrations of the additives. The results of FTIR suggested that both carboxylic acids were adsorbed onto the surface of the COM crystals. The zeta po-tential analysis showed a negative charge on the surface of the COM crystals in the mandelic acid medium, while the surface became more positive in the medium containing increasing concentrations of propane-1,2,3-tricarboxylic acid. In addition, an analysis was conducted to evaluate the thermal characteristics of the COM crystals prepared with and without the additives. The data obtained were used to calculate the kinetic parameters, such as the activation energy and pre-exponential factor, using the Coats-Redfern method. The calculated activation energies for stages I, II, and III in pure medium were 98.76, 270.69, 258.55 kJ/mol, respectively, which were lower than that of COM crys-tals prepared in the two media containing the additives.